Digital Report Dalam Upaya Peningkatan Mutu Pendidikan Pada Bimbingan Belajar Bright Education Kisaran - Ruri Ashari Dalimunthe; Iin Almeina Loebis; Muhammad Gusti Rivaldi (STMIK Royal, 2026)
Abstrak: Digital reports are technology-based reporting systems that function to record, process, and present information on students’ learning progress in a structured and real-time manner. This study aims to analyze the implementation of digital reports in improving the quality of educational services at the Bright Education tutoring institution in Kisaran. The method used is a descriptive approach by examining the utilization of digital systems in the students’ academic reporting process. The results of the study indicate that the use of digital reports is able to enhance transparency, administrative efficiency, and learning effectiveness. Through this system, data such as attendance, practice scores, evaluation results, and students’ learning progress can be well documented and accessed by various parties, including administrators, tutors, students, and parents. The implementation of the program at Bright Education Tutoring Institution has shown positive results and provided a significant impact on improving the quality of educational services. After the implementation of mentoring programs and the utilization of digital reports, the institution experienced improvements in academic data management, learning administration, and monitoring of student development in a more effective and structured manner. The activities carried out at Bright Education Tutoring Institution have successfully supported the transformation of educational administration toward a more modern, effective, and efficient system, thereby improving the quality of educational services within the tutoring environment. The activities carried out at Bright Education Tutoring successfully supported the transformation of educational administration into a more modern, effective, and efficient system through the implementation of digital reports. This innovation improved service quality, transparency, and students’ learning outcomes sustainably. Kata kunci: tutoring institution; digital report; information System Abstract: Digital report merupakan sistem pelaporan berbasis teknologi yang berfungsi untuk merekam, mengolah, dan menyajikan informasi perkembangan belajar siswa secara terstruktur dan real-time. Penelitian ini bertujuan untuk menganalisis penerapan digital report dalam meningkatkan mutu layanan pendidikan pada lembaga bimbingan belajar Bright Education Kisaran. Metode yang digunakan adalah pendekatan deskriptif dengan mengkaji pemanfaatan sistem digital dalam proses pelaporan akademik siswa. Hasil penelitian menunjukkan bahwa penggunaan digital report mampu meningkatkan transparansi, efisiensi administrasi, serta efektivitas pembelajaran. Melalui sistem ini, data seperti kehadiran, nilai latihan, hasil evaluasi, dan progres pemahaman siswa dapat terdokumentasi dengan baik dan diakses oleh berbagai pihak, termasuk pengelola, tutor, siswa, dan orang tua. Pelaksanaan program pada mitra Bimbingan Belajar Bright Education menunjukkan hasil yang positif dan memberikan dampak signifikan terhadap peningkatan mutu layanan pendidikan. Setelah diterapkannya program pendampingan dan pemanfaatan digital report, mitra mengalami peningkatan dalam pengelolaan data akademik, administrasi pembelajaran, serta monitoring perkembangan siswa secara lebih efektif dan terstruktur. Kegiatan pada mitra Bimbingan Belajar Bright Education berhasil mendukung transformasi administrasi pendidikan menjadi lebih modern, efektif, dan efisien melalui penerapan digital report. Inovasi ini meningkatkan kualitas layanan, transparansi, dan hasil belajar siswa secara berkelanjutan. Keywords: bimbingan belajar; rapor digital; sistem informasi